Numerical Modeling for the Effect of Soil Type on Stability of Embankment - Marwan Adil Hassan; Mohd Ashraf Mohamad Ismail; Heyam Hussein Shaalan (Civil Engineering Journal, 2021)
Dike construction has been widely used because of its potential to protect people and properties from overtopping flows. Water levels may exceed a dike crest and cause overtopping flow during high river discharge. This phenomenon has caused serious damage to the dike body due to the reduction of soil shear strength. The increase of water content within particles and its relationship with the development of breach channel failure in downstream and upstream slopes are affected by a series of geotechnical and hydraulic aspects. Transient seepage and slope stability analyses (FOS) were performed in this study using 2D finite element methods and time-history measurements under the effect of sandy and very silty sand soils. The numerical model of SLIDE 2018 was limited by its inability to incorporate all physical processes governing an overtopping breach failure. Numerical analyses were performed to simulate the development of pore pressures and water content at six positions in the dike’s upstream and downstream slopes in physical experimental tests using the van Genuchten Equation and the limit equilibrium method. The numerical results revealed that fine particles increase the pore water pressure and reduce the FOS. Appropriate dike design and maintenance are dependent on surrounding hydraulic conditions, dimensions, and soil types. Non-cohesive materials with fine particles were preferable. Doi: 10.28991/CEJ-SP2021-07-04 Full Text: PDF